Comparative study of leisure geography in Ahvaz metropolitan - Mostafa Mohammadi Dehcheshme; Nahid Sajadian; Ali shojaian; Narges Gheysari (تحقیقات کاربردی علوم جغرافیایی)
Study how to relax and leisure from the work of citizens it is located in the field of leisure geography studies. The current study is practical in an aim and descriptive– analytical in method and practical– theoretical in nature. In this study, the first path analysis model was used in order to express logical correlations between environmental and demographics variables, on leisure geography and providing structural analysis.the results of study path analysis model shows that the impacts of the physical environment outside the home with standardized coefficients0.461 into other variables have the greatest impact and demographic variables with standard coefficients 0.025 has least impact on leisure geography of metropolis. In the following, the number of 383 questionnaires was distributed in order to study comparatively the spatial pattern leisure geography among citizen's zones 2, 4 and 7 of the city of Ahvaz that they were at different levels of enjoyment. The results of the questionnaire of citizens indicate that leisure pattern in Region2 is different from other areas; However, the pattern of citizens leisure of district4 and7 has not a significant difference together. In this context, assigning a specific type of planning is approved in order to improve the quality of community health and welfare of the citizens;; with regard to natural and human environment conditions of the city and leisure facilities available.